1994
DOI: 10.1159/000170174
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology of Left Ventricular Hypertrophy in Dialysis Patients

Abstract: Left ventricular hypertrophy is a frequent cardiovascular alteration in end-stage renal disease patients on hemodialysis which is associated with increased morbidity and mortality. Hypertrophy results from chronic flow and pressure overload and from poorly understood neurohumoral alterations. Clinical symptomatology associated with ventricular hypertrophy is related to diastolic dysfunction which characterizes this condition. The symptoms are (1) an unusual sensitivity to volume changes such that hypotension a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 26 publications
0
22
1
Order By: Relevance
“…3 Uremic patients are at especially high cardiovascular risk, and LV hypertrophy, which is fundamentally determined by volume and pressure load 15 and accompanies combined LV dysfunction, is the main component of this risk. 16,17 Our study confirmed that LV hypertrophy is also a predictor of CHF events in patients on HD.…”
Section: Discussionmentioning
confidence: 99%
“…3 Uremic patients are at especially high cardiovascular risk, and LV hypertrophy, which is fundamentally determined by volume and pressure load 15 and accompanies combined LV dysfunction, is the main component of this risk. 16,17 Our study confirmed that LV hypertrophy is also a predictor of CHF events in patients on HD.…”
Section: Discussionmentioning
confidence: 99%
“…We only found a relation of LVH with PTH levels in the patients on short dialysis. Other factors contributing to LVH are age, hypervolemia, dialysis fistulae, and perhaps uremic toxins [52].…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] Thought to result from an increased cardiac load due to volume overload and altered peripheral resistance, [5][6][7][8] LVH is also an independent risk factor for mortality in dialysis patients. [1,9] Comparing treatment modalities, Enia et al [10] investigated European dialysis patients and found a higher degree of volume overload and more LVH in continuous ambulatory peritoneal dialysis (PD) as compared to hemodialysis (HD) patients. This was especially true of long-term PD patients, presumably due to a loss of residual renal function and thus an exacerbated volume overload.…”
Section: Introductionmentioning
confidence: 99%